Bidimensional Cross-Cloud Application Management with TOSCA and Brooklyn (summary) - Carrasco Mora, José Manuel; Cubo, Javier; Durán, Francisco; Pimentel-Sánchez, Ernesto (Salamanca University Press, 2016)
The diversity in the way different cloud providers offer their services, give their SLAs, present their QoS, support different technologies, etc., complicates the portability and interoperability of cloud applications, and favors vendor lock-in. Standards like TOSCA, and tools supporting them, have come to help in the provider-independent description of cloud applications. After the variety of proposed cross-cloud application management tools, we propose going one step further in the unification of cloud services with a deployment tool in which IaaS and PaaS services are integrated into a unified interface. We provide support for applications whose components are to be deployed on different providers, indistinctly using IaaS and PaaS services. The TOSCA standard is used to define a portable model describing the topology of the cloud applications and the required resources in an agnostic, and providers- and resources-independent way. We include in this paper some highlights on our implementation on Apache Brooklyn and present a non-trivial example that illustrates our approach. Resumen del artículo publicado en: Jose Carrasco, Javier Cubo, Francisco Durán, Ernesto Pimentel. Bidimensional Cross-Cloud Application Management with TOSCA and Brooklyn, 9th IEEE International Conference on Cloud Computing (CLOUD 2016), San Francisco, (EEUU). IEEE Computer Society, 2016.
Keywords: Aplicaciones informáticas; Cloud applications; Brooklyn; Cross-cloud; IaaS; PaaS; Multi-deployment; TOSCA